An early snapshot of plant–herbivore interactions: Psilophyton diakanthon sp. nov. from the Early Devonian of Gaspé (Quebec, Canada). Issue 1 (15th December 2022) - Colston, Courtney M.; Landaw, Kevin; Tomescu, Alexandru M. F.
Abstract: Premise: Trimerophytes are a plexus of early tracheophytes that form the base of the euphyllophyte clade and, thus, represent the link between the earliest land plants and modern‐day ferns, sphenophytes, and seed plants. As the best‐characterized trimerophyte, the genus Psilophyton occupies a key position in the euphyllophyte fossil record. We describe a new Psilophyton species that has implications for the evolution of plant–animal interactions. Methods: The fossil material is preserved by permineralization in the Lower Devonian (Emsian) Battery Point Formation (Québec, Canada) and was studied in serial sections using the cellulose acetate peel technique. Results: Psilophyton diakanthon sp. nov. differs from other Psilophyton species in possessing fibers that form a discontinuous layer in the inner cortex and two distinct types of spinescent emergences whose anatomy and morphology are consistent with roles in anti‐herbivore defense. Conclusions: Psilophyton diakanthon adds another species to an already diverse genus. Its two morphologically distinct types of spinescence suggest that herbivory was rampant in plant–animal interactions and demonstrate that anti‐herbivory defenses had reached a previously unrecognized level of sophistication by 400 million years ago, in the Early Devonian.